A percepção do aluno no curso de direito em relação ao bom professor - Possobon, Lauren Pons da Silva (2015)
Aware that the educational institutions are the place able to generate possibilities for significant social transformations, because they are able to contribute to the creation of a being more humane and developed, is that we felt the need to investigate the professor's image through the eyes of their students. This research aims to know what the students of law perceive from the pedagogical experience with their teachers. The locus of this study is the law course offered by three private higher education institutions based in the city of Cascavel / PR, being characterized as the environment in which the data were collected. The choice for the law school is due to the formation of the researcher, a lawyer, who had once worked as a teacher in this area. This academic experience has provided numerous contacts with students instigating to look at situations involving the juridical teacher, particularly on how the teachers relates with their students and crave the learning on classroom and, also, due to the small number of national surveys in the juridical education field that glimpse the teacher's image. To this research, the guiding question is: what are the characteristics of the good teacher in the law school in the view of their students? In the theoretical framework, we conducted a comparison on the conceptual dimensions and teachings of Pimenta and Anastasiou (2002), Zabalza (2004), Cunha (2005; 2007b), Tardif (2005), Veiga (2006) and Almeida (2012), among others authors that deal with the theme. We used a qualitative, exploratory and descriptive approach, manipulated from the literature study and field research with application of semi-structured questionnaires, answered by 180 students enrolled in the final years of law school, in the period from July to September of 2014. The research is, therefore, qualitative in the phenomenological perspective, once we seek to identify, through the converging evidence that had emerged from the data, the perceptions of the students in answers to the questions. We have chosen the rainbow as a metaphor, because our intention is to "colorize" the law school, enabling a lighter teaching environment and away from the excessive formality around the legal issues. The analysis of data showed that the good teacher for law school students must, among others, articulate, with an interdisciplinary approach, the content with the reality to form critical citizens, have pedagogical knowledge, be dynamic and enthusiastic, maintain a good relationship with the students inside and outside of school, have an academic training and must disclose satisfaction / love in teaching. We hope that by the end of this work and beyond the rainbow, the study will contribute as a way to new reflections and, mainly, for the teachers of law school rethink their practice providing better conditions of teaching / learning to their students, structuring one of the faces of teaching practice in Higher Education.